Predictors of pulmonary rehabilitation completion in the UK - Stone,PW; Hickman,KC; Steiner,MC; Roberts,CM; Quint,JK; Singh,SJ (ERJ Open Research, 2021)
Aim Determine characteristics of people with COPD associated with completion of pulmonary rehabilitation (PR).Methods Cross-sectional analysis of 7060 people with COPD enrolled in PR between 03/01/2017 and 31/03/2017. Data were from a UK national audit of COPD care. Factors associated with PR completion were determined using mixed-effects logistic regression with a random intercept for PR service. Factors chosen for assessment based on clinical judgement and data availability were: age, gender, country, SES, Body Mass Index (BMI), referral location, programme type, start within 90days, smoking status, oxygen therapy, GOLD stage, MRC grade, any exercise test, and any health status questionnaire.Results 4635 (66%) people with COPD completed a PR programme. People that were 60years or older, resident in Wales, referred within 90days, an ex- or never smoker, received an exercise test, or received a health status questionnaire had significantly greater odds of completing PR. People that were in the most deprived quintile, underweight or very severely obese, enrolled in a rolling rather than a cohort programme, had a higher GOLD stage, and had a higher MRC grade had significantly lower odds of completing PR.Conclusion People with COPD were more likely to complete PR when best-practice guidelines were followed. People with more severe COPD symptoms and those enrolled in rolling rather than cohort programmes were less likely to complete PR. Referring people with COPD in the earlier stages of disease, ensuring programmes follow best-practice guidelines, and favouring cohort over rolling programmes could improve rates of PR completion.